Efektivitas Media Audio Visual dalam Meningkatkan Partisipasi Siswa pada Materi Fiqih (Haji & Umroh) Kelas 10 di MA Mamba’ul Ma’arif - Safitri, Ika Rahma; Wahyudi, Wahyudi (Lembaga Yasin AlSys, 2025)
The low level of student participation in fiqih learning, particularly regarding the topics of Hajj and Umrah, poses a significant challenge in the instructional process at MA Mamba’ul Ma’arif. This condition is primarily influenced by the dominance of the lecture method and the limited variety of instructional media employed. This study aims to examine the effectiveness of audiovisual media in enhancing student participation. Employing a quantitative approach with a quasi-experimental design, the research involved 28 tenth-grade students from class X-B as participants. The instrument used was a student participation questionnaire administered before and after the intervention. The findings reveal a significant increase in participation, with an average score of 39.44 out of 45, equivalent to 87.64%, classified as a “High” level of participation. These results indicate that audiovisual media are effective in creating more engaging and interactive learning experiences, and in fostering greater student involvement in fiqih instruction. The implications of this study encourage educators to adopt audiovisual media as an innovative strategy for teaching procedural religious content.